Soy Isoflavones Inhibit Both GPIb-IX Signaling and αIIbβ3 Outside-In Signaling via 14-3-3ζ in Platelet - Ming Liu; Gan Wang; Runjia Xu; Chuanbin Shen; Heyu Ni; Ren Lai (Molecules, 2021)
Soy diet is thought to help prevent cardiovascular diseases in humans. Isoflavone, which is abundant in soybean and other legumes, has been reported to possess antiplatelet activity and potential antithrombotic effect. Our study aims to elucidate the potential target of soy isoflavone in platelet. The anti-thrombosis formation effect of genistein and daidzein was evaluated in ex vivo perfusion chamber model under low (300 s−1) and high (1800 s−1) shear forces. The effect of genistein and daidzein on platelet aggregation and spreading was evaluated with platelets from both wildtype and GPIbα deficient mice. The interaction of these soy isoflavone with 14-3-3ζ was detected by surface plasmon resonance (SPR) and co-immunoprecipitation, and the effect of αIIbβ3-mediated outside-in signaling transduction was evaluated by western blot. We found both genistein and daidzein showed inhibitory effect on thrombosis formation in perfusion chamber, especially under high shear force (1800 s−1). These soy isoflavone interact with 14-3-3ζ and inhibited both GPIb-IX and αIIbβ3-mediated platelet aggregation, integrin-mediated platelet spreading and outside-in signaling transduction. Our findings indicate that 14-3-3ζ is a novel target of genistein and daidzein. 14-3-3ζ, an adaptor protein that regulates both GPIb-IX and αIIbβ3-mediated platelet activation is involved in soy isoflavone mediated platelet inhibition.